Structural-chemical features and morphology of glauconites in sedimentary iron ore of Bakchar prospect (Western Siberia) - Rudmin, Maksim Andreevich; Reva, I.; Gunko, A.; Mazurov, Aleksey Karpovich; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
The research embraces the investigation results of glauconites in Bakchar iron ore occurrences to evaluate the potential diversified commercial application of this mineral. The following lab methods were used to analyze the morphology, chemical composition and structure of glauconites: granulometric analysis, optical microscopy, electron microscopy, X-ray fluorescence analysis, atomic arc-emission analysis and infrared spectroscopy. Glauconite was classified according to morphology and grain color and chemical composition and some specific characteristics were also determined (relative content of absorbed water, random distribution of smectite flakes within the grain structures). The research results showed that pistacho-green glauconite grains are less subjected to alteration than greenish-yellow grains due to the content of potassium, iron, absorbed water and organic impurities.
Keywords: структурно-химические особенности; морфология; глаукониты; железные руды; Западная Сибирь